2016
DOI: 10.1021/acs.cgd.6b00899
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Metamorphic InGaAs on GaAs (111)A: Counteracting Lattice Mismatch by Inserting a Thin InAs Interlayer

Abstract: We have successfully grown high quality In x Ga1–x As metamorphic layer on GaAs (111)­A using molecular beam epitaxy. Inserting a thin 3.0–7.1 monolayer (ML) InAs interlayer between the In0.25Ga0.75As and GaAs allowed the formation of a nearly lattice-relaxed In0.25Ga0.75As with a very flat upper surface. However, when the thickness of the inserted InAs is thinner or thicker than these values, we observed degradation of crystal quality and/or surface morphology. We also revealed this technique to be applicable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…11 The growth with InAs layers is also effective to improve the crystalline quality and surface morphology of the In 0.25 Ga 0.75 As film on the GaAs(111)A substrate. 12 This paper presents a systematic study on the GaSb heteropitaxy on GaAs(111)A using the InAs interlayer. We found that the strain evolution and growth mode drastically change with the InAs layer thickness.…”
Section: Introductionmentioning
confidence: 99%
“…11 The growth with InAs layers is also effective to improve the crystalline quality and surface morphology of the In 0.25 Ga 0.75 As film on the GaAs(111)A substrate. 12 This paper presents a systematic study on the GaSb heteropitaxy on GaAs(111)A using the InAs interlayer. We found that the strain evolution and growth mode drastically change with the InAs layer thickness.…”
Section: Introductionmentioning
confidence: 99%
“…In other QDs we measured values between 30 and 140 eV (not shown). These values are very large if compared with QDs grown on (111) substrates, where the three-fold symmetry of the crystal provides a more isotropic surface diffusion and a corresponding triangular or hexagonal nanostructure shape [ 26 , 27 , 35 , 36 , 41 , 42 , 46 , 61 , 68 , 69 , 70 , 71 ]. The origin of this splitting in (311)A QDs is attributed to asymmetries in the QDs shape that is affected by the anisotropy of the underlying crystal.…”
Section: Resultsmentioning
confidence: 99%
“…Within this class of QDs, droplet epitaxy (DE) [ 10 , 13 , 14 ] and droplet etching [ 9 , 15 , 16 ] (alternative growth protocols to Stranski–Krastanov for strain-free III–V-based semiconductor nanostructures), enabled the fabrication of state-of-the-art devices such as lasers [ 17 , 18 , 19 , 20 , 21 ] and quantum emitters, including single-photon sources [ 22 , 23 , 24 , 25 , 26 ] and entangled photons [ 9 , 27 , 28 , 29 , 30 ] with electrical injection [ 31 ]. The versatility of this method allowed to grow many different semiconductor alloys (GaInSb [ 32 ], AlGaAs [ 33 , 34 , 35 , 36 , 37 ], InGaAs [ 38 , 39 , 40 , 41 , 42 , 43 , 44 ], and InGaP [ 26 , 45 , 46 ]), forming a plethora of nanostructures [ 47 ] such as quantum dots (QDs); QDs diads [ 48 , 49 , 50 ]; multiple-concentric quantum rings [ 18 , 23 , 51 , 52 ...…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As ternary III‐V compounds, In x Ga 1 − x As (0 < x < 1) films with relatively high carrier density, wide direct band gap from 0.35 to 1.42 eV, high reliability and radiation resistance have been widely applied into optical and electronic devices, such as short‐wave infrared photodetectors, light‐emitting diodes, lasers, solar cells, and high‐mobility transistors . With the recent technical development, various epitaxial growth technologies such as physical vapor deposition (PVD), liquid phase epitaxy (LPE), molecular beam epitaxy (MBE), and metal‐organic chemical vapor deposition (MOCVD) have been explored to prepare high‐performance thin‐film semiconductors .…”
Section: Introductionmentioning
confidence: 99%